2015
DOI: 10.1186/s13030-014-0028-7
|View full text |Cite
|
Sign up to set email alerts
|

Absence of change in the gray matter volume of patients with ulcerative colitis in remission: a voxel based morphometry study

Abstract: BackgroundRecent neuroimaging studies have investigated the brain involvement in patients with Crohn's disease (CD) and Ulcerative Colitis (UC). Functional studies found abnormalities in cognitive and emotional functions in CD and UC, while a voxel based morphometry (VBM) study found morphological changes in CD. We conducted a VBM study to compare the gray matter (GM) volume of UC patients and controls.MethodsEighteen UC patients in remission and eighteen healthy controls underwent structural MRI. VBM is a ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Given the originality of the present research, it is not possible to compare these results with those that could be obtained in other groups of patients undergoing CABG or other cardiac surgeries. Some studies have investigated the relationship of preoperative anxiety and depression symptoms of patients undergoing cardiac surgeries with complications and PO mortality, but the PO period varied widely among the studies, in addition to the lack of consensus on the best or more indicated tool to evaluate the symptoms of anxiety and depression ( 11 - 14 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the originality of the present research, it is not possible to compare these results with those that could be obtained in other groups of patients undergoing CABG or other cardiac surgeries. Some studies have investigated the relationship of preoperative anxiety and depression symptoms of patients undergoing cardiac surgeries with complications and PO mortality, but the PO period varied widely among the studies, in addition to the lack of consensus on the best or more indicated tool to evaluate the symptoms of anxiety and depression ( 11 - 14 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In international studies, researchers investigated the association between preoperative anxiety and depression symptoms with PO complications, with a focus on mortality up to 30 days after surgery ( 11 - 14 ) . In the present study, we chose to investigate the presence of complications and death in the PO period, during the patients’ stay in the Intensive Care Unit (ICU).…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to Japanese circumstances surrounding patients with eating disorders and their families. At present, both in-patient and outpatient treatment facilities for eating disorders are quite insufficient [ 33 ] and day-patient treatments are rarely available for eating disorders. Therefore, it is not rare that patients stay home almost all day and their families have to take care of the patients for long hours that may lead to their mental exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…In their attempts to control childhood asthma, parents engage in a variety of asthma management activities, including compliance with medical treatments [ 7 ], monitoring their child’s asthma symptoms, and coordinating family routines to avoid environmental triggers [ 8 , 9 , 10 ]. Generally, when compared with parents of healthy children, parents of children with asthma experience a greater level of stress [ 11 ], anxiety, and depressive symptoms [ 12 ].…”
Section: Introductionmentioning
confidence: 99%